(untitled) (Physical Education, Health and Social Sciences, 2025)
Food Mushrooms with kitchen and nutritional value multipurpose applications are the features that enable every country. They are highly regarded by health-conscious people and are biased in terms of fat and calories, but are rich in protein, fiber, vitamins and minerals. Most of them are kept as Pleurotus ostreatus, Agaricus bisonus, and Lentinula Edoden. Mushroom consumption is examined to learn how to use it in medicine, including foods such as antibacterial, antioxidant, and immunomodulatory effects. Organic farming and biotechnology benefit more by increasing the number of more edible fungi that benefit the economy and well-being of human life.